Formation and structural features of micelles formed by surfactin homologues - Bochynek, Michał; Lewińska, Agnieszka; Witwicki, Maciej; Dębczak, Agnieszka; Łukaszewicz, Marcin (Frontiers in Bioengineering and Biotechnology, 2023)
Surfactin, a group of cyclic lipopeptides produced by Bacillus subtilis, possesses surfactant properties and is a promising natural and biologically active compound. In this study, we present a comprehensive characterization of surfactin, including its production, chromatographic separation into pure homologues (C12, C13, C14, C15), and investigation of their physicochemical properties. We determined adsorption isotherms and interpreted them using the Gibbs adsorption equation, revealing that the C15 homologue exhibited the strongest surface tension reduction (27.5 mN/m), while surface activity decreased with decreasing carbon chain length (32.2 mN/m for C12). Critical micelle concentrations (CMC) were also determined, showing a decrease in CMC values from 0.35 mM for C12 to 0.08 mM for C15. We employed dynamic light scattering (DLS), transmission electron microscopy (TEM), and density functional theory (DFT) calculations to estimate the size of micellar aggregates, which increased with longer carbon chains, ranging from 4.7 nm for C12 to 5.7 nm for C15. Furthermore, aggregation numbers were determined, revealing the number of molecules in a micelle. Contact angles and emulsification indexes (E24) were measured to assess the functional properties of the homologues, showing that wettability increased with chain length up to C14, which is intriguing as C14 is the most abundant homologue. Our findings highlight the relationship between the structure and properties of surfactin, providing valuable insights for understanding its biological significance and potential applications in various industries. Moreover, the methodology developed in this study can be readily applied to other cyclic lipopeptides, facilitating a better understanding of their structure-properties relationship.